(untitled) (Journal of the College of Basic Education, 2022)
This study is an attempt to explore the major social and moral concerns of Edward Albee (1928- ) in two of his famous plays: Who’s Afraid of Virgini a Woolf ? and The Death of Bessie Smith . In these plays, Albee reveals his protest against corrupt cultural values and the false concept of manhood and womanhood . He also exposes the perverted husband-wife relationships which lead to frustrations and nightmares .The themes of social inequality, racial distinction , loss and death are never absent of Albee’s mind. In his representations of the American social life , Albee focuses on the artificial nature of many human relationships in his society .